The Effect of an Online Professional Development Program on Computer Accessibility, Teaching Proficiency, and Motivation Among Educators in Higher Education in Pakistan - Thakur, Ibtasam Thakur; Asmaa Azeem*; Moafia Nadar (JCTE, 2024)
The main purpose of conducting this study was to determine the effects of online professional development courses on teachers’ computer access, teaching skills, and motivation in higher education. This was a quantitative study based on a descriptive research design that collected data through a questionnaire. The population of this study was consisted of teachers of public and private colleges of Narang Mandi city of Punjab, Pakistan. The sample of this study was obtained from four public and four private colleges of Narang Mandi. The sample size was 200 teachers. The researcher adopted the stratified sampling method to select a representative sample. Independent sample t-test and one-way ANOVA were used to investigate the effects of an online professional development course on teachers’ computer access, teaching skills, and motivation in higher education. Findings underscore the substantial benefits of online professional development courses in equipping educators with the necessary tools and skills to thrive in the dynamic landscape of higher education, ultimately contributing to the enhancement of their teaching effectiveness and motivation.